VD_FINDINFO Décision / 2015 / 97 vom 2. Februar 2015 - VD Tribunal cantonal (2015)
DÉTENTION POUR DES MOTIFS DE SÛRETÉ, PROPORTIONNALITÉ, RISQUE DE RÉCIDIVE, SOUPÇON | 212 al. 3 CPP (CH), 220 CPP (CH), 221 al. 1 let. c CPP (CH)